Pengaruh Metode Drill Terhadap Kemampuan Menulis Karangan Deskripsi Siswa di SD Negeri 81 Palembang - Dewi, Shanti; Hermansah, Bambang; Ayurachmawati, Puji (ANTHOR: Education and Learning Journal, 2022)
This study discusses the effect of using the drill method (practice) on the ability to write descriptive essays for fourth grade students at SD Negeri 81 Palembang. The purpose of this study was to determine the effect of using the drill method (practice) on the ability to writedescriptive essays for fourth grade students. The type of research used is Quasi Experimental and the research method used by the researcher is quantitative. The type of design used in this study is "Nonequivalent Control Group Design". Sources of data or instruments used by researchers are tests and documentation. The research data analysis techniques used were normality test, homogeneity test and hypothesis testing. The population in this study was class IV with 32 students from class IVA and 32 students from class IVB used as the subject. Basedon the results of the pretest research in the experimental class, the average value before being given treatment using the drill method was 52.41 and the average value after being given treatment using the drill method was 90.31.